Export or Domestic-Led Growth in Asia? - Jesus Felipe; Joseph Lim (Asian Development Bank (ADB), 2005)
In recent years, some developing Asian countries claim to have started shifting emphasis from export-led to domestic-demand-led growth policies with a view to achieving a more balanced growth strategy. This paper evaluates empirically how far this shift has gone. The evaluation - based on an analysis of five countries - finds no evidence that the period 1993–2003 has been marked by such a shift at the expense of a decline in net exports. It also finds that periods of expansionary domestic demand and deteriorating net exports signaled an ensuing crisis. This should serve as an early warning system.
hdl:11540/1898
Keywords: 330; Wirtschaftswachstum; Wachstumspolitik; Exportinduziertes Wachstum; China; Indien; Südkorea; Philippinen; Thailand